2018
DOI: 10.1371/journal.pone.0190157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of small-sided games with different levels of opposition on the tactical behaviour of young footballers with different levels of sport expertise

Abstract: To optimize players' tactical abilities, coaches need to design training sessions with representative learning tasks, such as, small-sided games. Moreover, it is necessary to adapt the complexity of the tasks to the skill level of the athletes to maximally improve their perceptual, visual and attentive abilities. The objective of this study was to analyze the effect of two teaching programs, each utilizing modified games with varied levels of opposition, on decision-making and action execution in young players… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 47 publications
0
67
1
9
Order By: Relevance
“…Our results indicated greater values for defensive superiority, considerably different from those observed in literature studies that have focused on evaluating games with numerical equality [1,5,12,14]. On the other hand, Práxedes et al [9] showed that a training program using numerical superiority was better to improve the decision making in U12 players than a numerical equality program. therefore, further studies may investigate numerical inferiority/superiority in accordance with the space configuration reported in the present study and the consequences in physical, technical, and tactical demands of the match.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results indicated greater values for defensive superiority, considerably different from those observed in literature studies that have focused on evaluating games with numerical equality [1,5,12,14]. On the other hand, Práxedes et al [9] showed that a training program using numerical superiority was better to improve the decision making in U12 players than a numerical equality program. therefore, further studies may investigate numerical inferiority/superiority in accordance with the space configuration reported in the present study and the consequences in physical, technical, and tactical demands of the match.…”
Section: Discussioncontrasting
confidence: 99%
“…SSGs improve the physical, technical, and tactical dimension simultaneously [2]. Recently, studies have focused on the effects of different SGG formats and task conditions on changes in the physiological [1,[3][4][5], technical [3,4,6], physical [7,8], and tactical performance [4,6,9,10], on manipulating the space, the number of players, the number of ball touches per player [1,[4][5][6][7][9][10][11][12], and on the impact of training programs involving SSGs [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 10 studies that analyzed the effects of training programs on decision-making (Table 4), 4 of them used a nonlinear pedagogy-based program to induce changes in the decisions made by participants [29,30,51,52]. Three of the studies used immersive three-dimensional videos to stimulate the decisions made by participants [22,53,54], and two of the studies used video feedback and questioning [48,49].…”
Section: Effects Of Decision-making-based Training Programsmentioning
confidence: 99%
“…The study design consisted of an intragroup design, from a quasiexperimental methodology, where two research phases were considered. In the first phase, named preintervention phase, the values of decision-making and execution were recorded for the defensive actions analyzed [decision-making (DM) and execution (Ex)] in three competition matches, as indicated by previous studies (Práxedes et al, 2018b). This first measurement allows to establish the previous level of the players.…”
Section: Design and Proceduresmentioning
confidence: 99%